Implementation of the Land Swap Agreement (Ruislag) for Waqf Land for the Construction of a Toll Road - Umi Masnur Adniyah (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to determine the process of implementing land swap agreements for waqf land used for toll road construction and to analyze the government's responsibilities in the implementation of the swap. The research method used is empirical juridical, interviewing directly the land owners, Nazhir, and the Office of Religious Affairs. The novelty of this study is the swap of waqf land to be built as public facilities in the form of a toll road with the assistance of Nazhir and the Office of Religious Affairs. The novelty of this research lies in the application of information technology and digital management systems to accelerate and simplify the ruislag (land exchange) procedure for waqf land. This may involve the use of digital platforms that enable more transparent and efficient monitoring processes and facilitate better communication between relevant parties such as the nazhir, the Ministry of Religious Affairs, the Indonesian Waqf Board (BWI), and the land office. The results of this study indicate that the implementation of the land exchange agreement for endowed land is carried out by the Nazhir, the District Religious Affairs Office (KUA), and the local District Land Office. The exchange process involves replacing the endowed land with land of equal or higher value. The conclusion drawn is that when the exchange is carried out, the Nazhir, as the administrator, must be transparent and prepare all necessary documents with the assistance of IWN to measure the evaluation instruments developed to assess the performance of waqf management at the national level, from waqf management, regulations, institutions, processes, systems, to results and impacts. while the guidelines used are Law Number 41 of 2004 on Endowment and Law Number 2 of 2012 on Land Acquisition for Public Interest Development.